Systemic inflammation, blood-brain barrier vulnerability and cognitive / non-cognitive symptoms in Alzheimer disease: Relevance to pathogenesis and therapy - Takeda, Shuko; Sato, Naoyuki; Morishita, Ryuichi (Frontiers in Aging Neuroscience, 2014)
The incidence of dementia is increasing at an alarming rate, and has become a major public health concern. Alzheimer disease (AD) is the most common form of dementia and is characterized by progressive cognitive impairment. In addition to classical neuropathological features such as amyloid plaques and neurofibrillary tangles, accumulation of activated immune cells has been documented in the AD brain, suggesting a contribution of neuroinflammation in the pathogenesis of AD. Besides cognitive deterioration, non-cognitive symptoms, such as agitation, aggression, depression and psychosis, are often observed in demented patients, including those with AD, and these neuropsychological symptoms place a heavy burden on caregivers. These symptoms often exhibit sudden onset and tend to fluctuate over time, and in many cases, they are triggered by an infection in peripheral organs, suggesting that inflammation plays an important role in the pathogenesis of these non-cognitive symptoms. However, there is no mechanistic explanation for the relationship between inflammation and neuropsychiatric symptoms. Observations from experimental mouse models indicate that alteration of brain blood vessels, especially blood-brain barrier dysfunction, may contribute to the relationship. The current review summarizes the results from recent studies on the relationship between inflammation and AD, while focusing on cerebrovascular alterations, which might provide an insight into the pathogenesis of cognitive / non-cognitive symptoms in AD patients and suggest a basis for the development of new therapeutic treatments for these conditions.